Coffe and Parkinson disease - Fajemidagba Grace Ayobami (Progress in Brain Research, Elsevier, 2024)
Parkinson's disease (PD) is a prevalent neurodegenerative disease marked by dopaminergic neuronal loss and misfolded alpha-synuclein (α-syn) accumulation, which results in both motor and cognitive symptoms. Its occurrence grows with age, with a larger prevalence among males. Despite substantial study, effective medicines to reduce or stop the progression of diseases remain elusive. Interest has grown in examining dietary components, such as caffeine present in coffee, for potential medicinal effects. Epidemiological studies imply a lower incidence of PD with coffee drinking, attributable to caffeine's neuroprotective abilities. Beyond caffeine, coffee constituent like chlorogenic acid and cafestol have anti-Parkinsonian benefits. Moreover, coffee use has been related with variations in gut microbiota composition, which may reduce intestinal inflammation and prevent protein misfolding in enteric nerves, perhaps through the microbiota-gut-brain axis. This review gives a summary of the neuroprotective effects of coffee, investigating both its motor and non-motor advantages in individuals with PD as well as in experimental models of PD. We reviewed some bioactive constituents of coffee, their respective interactions with misfolded α-syn accumulation, and its emerging mechanisms associated to the gut microbiome.